BROOKE DOCKYARD IT ASSET MANAGEMENT SYSTEM - Nina, Sudi (Universiti Malaysia Sarawak, (UNIMAS), 2023)
In this era of globalization, the concept of digital form is increasing use among the organization to ensure their business run smoothly. However, the IT Department of BDEWC is still using a manual approach to manage over a thousand IT assets, including hardware, software, and network stuff. Therefore, this project develops the Brooke Dockyard IT Asset Management System to replace the traditional paper form-based to web-based forms. This system allowed users to track, manage, and store their asset information. In addition, this thesis covered the development and implementation of a web-based application for BDEWC's IT Department at Sejingkat Fabrication Yard. The Rapid Application Development model was chosen as the project's methodology.